Teleologia i teologia. Nowożytne przemiany w rozumieniucelowości natury ludzkiej na przykładzie Kajetana i Lutra - Andrzej Persidok (Warszawskie Studia Teologiczne)
The problem of the ultimate goal of man belongs to the most important issues of Western theological anthropology. Traditionally, it was perceived according to the model of a harmonious relation between nature and grace: man is by nature unable to find fulfillment elsewhere than in supernatural communion with God. The ultimate goal of his nature is the supernatural goal, which is reflected in his “natural desire to see God” – the hidden driving force of his entire activity. This conviction, shared by both patristic and medieval theology, at the dawn of modernity undergoes profound transformation, and in time it becomes lost. The purpose of this study is to present these changes in understanding the finality of human nature on the example of two important representatives of early modern theology: Cardinal Kajetan and Martin Luther. The first of them, excessively succumbing to the influence of Aristotle's philosophy, introduced into theology a concept of "pure nature", indifferent to any supernatural complement. The second, parting from the conviction about the total destruction of human nature by sin, in the place of harmony between human nature and its supernatural goal introduced the relation of a violent opposition. On the example of these two extremely different thinkers, one can observe how in modern theology takes place the destruction of the classical notion of finality and the separation between the supernatural goal and human nature with its internal dynamism.